(NrASSKAZY(B, (NFELXETONY(B, (NPAMFLETY(B: [1901-1912] / s (N~ASTX (B1s - (NgA[EK(B, (NqROSLAWs ((NmOSKWA(B: s (NpRAWDA(B, s, 1985)
(Nw PERWYJ TOM sO^INENIJ ^E[SKOGO PISATELQ qROSLAWA gA[EKA (B(1883-1923) (NWO[LI RASSKAZY(B, (NFELXETONY(B, (NPAMFLETY(B, (NNAPISANNYE W (B1901-1912 (NGODAH(B.s
rus
Keywords: (NrASSKAZY(B, (NPOWESTIs; (NfELXETONYs -- (NpAMFLETYs